Welcome the Stranger Within - Snowber, Celeste Nazeli (Art/Research International, 2025)
Welcome the stranger within is a short video danced poem which draws on embodied and poetic ways of inquiry to express the welcoming of all parts of oneself. Integrating contemporary dance and poetry, it is a site-specific performance taken on Denman Island in British Columbia, Canada. The performer, Celeste Nazeli Snowber, explores how one can have a call and response with the earth and open an embodied understanding through cultivating a relationship with body, land, water and what it means to be human.